2021
DOI: 10.1111/nep.13850
|View full text |Cite
|
Sign up to set email alerts
|

A psychosocial intervention for individuals with advanced chronic kidney disease: A feasibility randomized controlled trial

Abstract: Aim The current study evaluated the feasibility and preliminary efficacy of a psychosocial intervention, the Kidney Optimal Health Program, in reducing symptoms of depression and anxiety in individuals with advanced chronic kidney disease. Methods Patients with stage 4 or 5 chronic kidney disease were randomized to either a nine‐session psychosocial intervention programme or usual care. Feasibility was assessed through recruitment and retention rates and programme acceptability. Participants completed assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Despite an increasing number of self-management interventions tested through research (Donald et al, 2021;Jenkins et al, 2021;M. C. Lee, Wu, et al, 2021;Morris & Lycett, 2021) patients are still experiencing unmet needs in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increasing number of self-management interventions tested through research (Donald et al, 2021;Jenkins et al, 2021;M. C. Lee, Wu, et al, 2021;Morris & Lycett, 2021) patients are still experiencing unmet needs in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research suggested that favorable hemodialysis requires patients to precisely control their fluid intake and diet, which greatly changes the patients' previous living habits [7][8][9][10][11][12][13][14][15][16][17][18]. Most patients refuse to receive the long-term hemodialysis treatment psychologically and therefore they tend to generate some negative moods (including depression and anxiety) [19]. As a result, they respond negatively to the treatment and behave with poor compliance, thus influencing the blood glucose control, overall treatment outcome, and prognosis [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This approach challenges traditional methods of health care by encouraging patients to be actively involved in their own management [56] as this is anticipated to be more effective than using passive approaches [57]. The OHP has been shown to be beneficial for people with other chronic conditions such as diabetes [58], stroke [59], and chronic kidney disease [60]. However, no research has yet evaluated its use in patients with long COVID.…”
Section: Introductionmentioning
confidence: 99%